The Relationship Between State Loneliness and Depression Among Youths During COVID-19 Lockdown: Coping Style as Mediator - Zhang, Yayun; Huang, Lin; Luo, Yuejia; Ai, Hui (Frontiers in Psychology, 2021)
COVID-19 pandemic has a great impact on public mental health. However, loneliness during the lockdown relate to depression and whether the relationship would be mediated by coping style or whether sex moderate loneliness and coping style are not clear. The study was aimed to examine the mediating role of coping style in the relationship between state loneliness and depression as well as the moderating role of sex in the relationship between state loneliness and coping styles during the lockdown of COVID-19. Participants were 337 college students in China during the COVID-19 pandemic (January to February, 2020). State of depression and anxiety, state loneliness, coping styles to COVID-19 were measured. The results showed that loneliness was an effective predictor of depression during self-quarantine. Moreover, coping style mediated the relationship between state loneliness and depression. While sex did not moderate the relationship between state loneliness and coping style. Youths were inclined to use more positive coping strategies than negative coping strategies. Our results indicate less loneliness is an effective way to relieve depression, and coping strategies, especially the positive ones, are important for youths to prevent depression and loneliness during the lockdown of the COVID-19 pandemic.